Effects of sub-lethal doses of fentanyl on vital physiologic functions and withdrawal-like behaviors in adult goats - Neumueller, Suzanne E.; Buiter, Nicole; Hilbert, Grace; Grams, Kirstyn; Taylor, Reiauna; Desalvo, John; Hodges, Grace L.; Hodges, Madeline M.; Pan, Lawrence G.; Lewis, Stephen J.; Forster, Hubert V.; Hodges, Matthew R. (Frontiers in Physiology, 2023)
Synthetic opioids like fentanyl have improved the standard of care for many patients in the clinical setting, but their abuse leads to tens of thousands of overdose deaths annually. The current opioid epidemic underscores a critical need for insights into the physiological effects of fentanyl on vital functions. High doses of opioids in small mammals cause opioid-induced respiratory depression (OIRD) leading to hypoventilation, hypoxemia, and hypercapnia. In addition, opioids can also increase the alveolar to arterial oxygen (A-a) gradient and airway dysfunction. However, little is known about the physiologic effects of sub-lethal doses of opioids in large mammals. Here we report the effects of a sub-lethal dose range of fentanyl (25-125 µg/kg; IV) on vital physiologic functions over 90 minutes (min) and withdrawal-like behaviors over the subsequent 4 hours (h) in adult female goats (n=13). Fentanyl induced decreases in breathing frequency in the first few min post-injection, but then led to a sustained increase in tidal volume, total ventilation, and blood pressure with a reduced heart rate for ≥ 90 min. These ventilatory changes resulted in time-dependent arterial hypocapnia and hypoxemia and an increased alveolar to arterial oxygen gradient ~30 min post-injection indicative of impaired gas exchange in the lung. The predominant effects of fentanyl on breathing were stimulatory, underscored by an increased rate of rise of the diaphragm muscle activity and increased activation of upper airway, intercostal and abdominal muscles.. Beginning 90 min post-injection we also quantified withdrawal-like behaviors over 4h, demonstrating dose- and time-dependent increases in locomotor, biting, itching, and pawing behaviors. We conclude that fentanyl at sublethal doses induces multiple physiologic and behavior changes that emerge along different time courses suggesting multiple independent mechanisms underlying effects of opioids.